Conjunctival Microbiota in Patients With Type 2 Diabetes Mellitus and Influences of Perioperative Use of Topical Levofloxacin in Ocular Surgery - Zhu, Xiangjia; Wei, Ling; Rong, Xianfang; Zhang, Yinglei; Zhang, Qian; Wen, Xiaofeng; He, Wenwen; Zhang, Keke; Chen, Feng; Wei, Lai; Lu, Yi (Frontiers in Medicine, 2021)
Background: Patients with type 2 diabetes mellitus (T2DM) are prone to ocular surface infections and endophthalmitis after ocular surgeries. We therefore characterized the conjunctival microbiome of T2DM patients and influence of perioperative levofloxacin to investigate whether a dysbiosis is associated with this phenomenon. Methods: Conjunctival microbiome of 79 T2DM patients and 113 non-diabetic controls was profiled using the 16S rDNA sequencing approach. Furthermore, 21 T2DM and 14 non-diabetic patients who underwent cataract surgeries were followed up in 5 weeks postoperatively and the influence of perioperative levofloxacin on the conjunctival microbiome was further investigated prospectively and compared longitudinally. Results: The α-diversity of the conjunctival microbiota was significantly higher in T2DM patients than in controls (P <0.05). Significant differences in both composition and function of the conjunctival microbiome were identified on the ocular surface of T2DM patients as compared to non-diabetic controls. Particularly, phylum Bacteroidetes and Fusobacteria, genus Pseudomonas, Haemophilus, and Empedobacter were enriched, while genus Streptococcus was reduced on the T2DM ocular surface. Microbial genes functioning of bacterial chemotaxis was elevated in the conjunctival microbiome of T2DM patients. Furthermore, compared to the initial status, several genera including Staphylococcus were more enriched in the conjunctival microbiome of T2DM patients after 3-days use of preoperative levofloxacin topically, while no genus was more enriched in the non-diabetic follow-up group. No difference was observed between initial status and 7 days after ceasing all postoperative medications in both follow-up groups. Conclusions: The conjunctival microbiome of T2DM patients was more complex and might be restored to the initial status in a short period after cataract surgery.